ANALISA FAKTOR PENYEBAB KETERLAMBATAN PROGRESS TERKAIT DENGAN MANAJEMEN WAKTU (Studi Kasus: Pelaksanaan Pembangunan Gedung UPT PP Politeknik Negeri Semarang) - ABDUL M, AZIZ; RIYANDI W, MARTHEN; S.T., M.T., DIANITA RATNA K; Ir., NUGROHO HARTONO (Politeknik Negeri Semarang, 2016)
One of the most important problems in the implementation of the construction project is a delay the project schedule related to decreased work performance or progress. Delays occurred in almost every project work and have a different problem. Delays in project implementation are always consequences are quite harmful to the users and service providers, due to the impact of delays in the project is a conflict and debate about who and what is the cause. This research was conducted in order to obtain or determine the factors that influence delays in the completion of construction projects. The case study of this research is the building project UPT-PP Semarang State Polytechnic. The method used in this study was descriptive qualitative method. The instrument used in this study through a survey method (questionnaire), the first collected data from the study of literature is followed by interview (interview) to the relevant parties. To rank the factors that cause delays, AHP (Analytical Hierarchy Process) is used sa means of calculating the data questionnaire. The results of data analysis showed that there are four main factors that influence delays in construction projects, sequentially starting from the biggest culprit as follows: (1) delays in delivery of materials, (2) design errors by planners, (3) labor productivity is low, (4) inaccuracy when ordering the goods.Kata kunci : delay in the project, factor, progress, building construction.